Return to Dien Bien Phu and other stories (Foreign Languages Publishing House, 1961)
These stories reflect some of the features of the life of the armymen of the Democratic Republic of Vietnam: their struggles, training, productive labour, education, love, ect. They are an expression of the literary movement in the Vietnam people's army